2019
DOI: 10.17305/bjbms.2019.3713
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated expression of MNX1-AS1 long noncoding RNA predicts poor prognosis in gastric cancer

Abstract: As important regulators of gene expression long noncoding RNAs (lncRNAs) are implicated in various physiological and pathological processes, including cancer. An oncogenic role of MNX1 antisense RNA 1 (MNX1-AS1) lncRNA has been suggested in cervical cancer and glioblastoma. In this study, we investigated the clinicopathological significance and biological function of MNX1-AS1 in gastric cancer (GC). The expression of MNX1-AS1 was analyzed by qRT-PCR in 96 GC and adjacent non-tumor tissues in relation to clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
(34 reference statements)
2
17
0
Order By: Relevance
“…Currently, the expression pattern and functional role of lncRNA MNX1-AS1 in diverse tumours have been gradually identified [22,24,44,45] Yang et al found that overexpression of MNX1-AS1 exerted tumourpromoting roles in lung adenocarcinoma [45]. A current study by Ji et al showed that enrichment of MNX1-AS1 is strongly linked to TNM stage in hepatocellular carcinoma (HCC) patients [46].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the expression pattern and functional role of lncRNA MNX1-AS1 in diverse tumours have been gradually identified [22,24,44,45] Yang et al found that overexpression of MNX1-AS1 exerted tumourpromoting roles in lung adenocarcinoma [45]. A current study by Ji et al showed that enrichment of MNX1-AS1 is strongly linked to TNM stage in hepatocellular carcinoma (HCC) patients [46].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 882 patients from the all eligible articles were included to evaluate prognostic value of MNX1-AS1 (presented in Table 1). All articles covered gastric cancer(GC) (n = 3) [8][9][10], lung cancer (LC) (n = 3) [6,20,21], other cancer(n = 3) including: esophageal squamous cell carcinoma (ESCC), cervical cancer (CC), epithelial ovarian cancer (EOC) [14,18,22].…”
Section: Search Results Of Eligible Studiesmentioning
confidence: 99%
“…Discussion MNX1-AS1, also known as MAYA and CCAT5, is located at chromosome 7q36.3 [6]. Upregulation of MNX1-AS1 expression has been found in a variety of cancers, including gastric cancer [8][9][10], lung cancer [6,20,21], esophageal squamous cell carcinoma [14,15], and estrogen-dependent cancer [7,18,22], etc. MNX1-AS1 play a role of functional oncogene in addition to activating AKT/mTOR pathway and its natural sense transcript MNX1 in breast cancer cells, it also promotes the process of EMT [7].…”
Section: Involvement Of Mnx1-as1 In Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, AGAP2-AS1 could participate as an epigenetic repressor of E-cadherin expression. As shown in Figure 3 , several other lncRNAs (Lnc01614, LOC554202, TUG1, AFAP1-AS1, NEAT, MNX1-AS1, AOC4P, SNHG20, CCAT1, TPT1-AS1, and LINC00941) have been found to be upregulated and associated with poor prognosis in clinical samples of GC [ 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ]. The knockdown of these lncRNAs was associated with the re-expression of E-cadherin.…”
Section: Noncoding Rnas: Classification and Functionsmentioning
confidence: 99%